2010
DOI: 10.1186/1472-6955-9-10
|View full text |Cite
|
Sign up to set email alerts
|

Oncology patients' and professional nurses' perceptions of important nurse caring behaviors

Abstract: BackgroundCaring is the essence of nursing. Caring to be meaningful needs to be based on mutual agreement between nurses and patients as to what constitutes nurse caring behaviors. As a result, healthcare professional can enhance patients' satisfaction of care by providing appropriate caring behavior. However, previous research that combined multiple types of patients, nurses and institutions demonstrated disagreement in prioritizing important behaviors. This paper reports a study that aimed at determining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
2
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 24 publications
(56 reference statements)
7
70
2
12
Order By: Relevance
“…En cuanto a las conductas de cuidado estudiadas en el grupo de enfermeras, destaca que a pesar de ser considerada como más importante la categoría "monitorea y hace seguimiento", la conducta "administra los tratamientos y medicinas oportunamente" perteneciente a la categoría "accesible" se ubica en primer lugar, alcanzando la mayor media de las 50 conductas estudiadas. Para otros estudios (22,24,25) esta conducta no es prioritaria, con excepción del estudio de Zamanzadeh et al (10), en donde esta conducta también se considera como la primera elección.…”
Section: Discusión Y Conclusiónunclassified
See 3 more Smart Citations
“…En cuanto a las conductas de cuidado estudiadas en el grupo de enfermeras, destaca que a pesar de ser considerada como más importante la categoría "monitorea y hace seguimiento", la conducta "administra los tratamientos y medicinas oportunamente" perteneciente a la categoría "accesible" se ubica en primer lugar, alcanzando la mayor media de las 50 conductas estudiadas. Para otros estudios (22,24,25) esta conducta no es prioritaria, con excepción del estudio de Zamanzadeh et al (10), en donde esta conducta también se considera como la primera elección.…”
Section: Discusión Y Conclusiónunclassified
“…y manipular equipos de uso parenteral (sueros), las máquinas de aspiración y otros equipos que hayan en el servicio" perteneciente a la categoría "monitorea y hace seguimiento", coincide con el estudio de Zamanzadeh et al (10), en donde queda ubicado en la misma posición, sin embargo en el estudio de Larsson et al (5) esta conducta también se menciona dentro de las cuatro primeras posiciones.…”
Section: Discusión Y Conclusiónunclassified
See 2 more Smart Citations
“…Research Zamanzadeh, et al (2010) showed that aspects of competence in the implementation of nursing care that is needed is to assess the patient's state of the patient, making it easier to determine what is needed for the patient and easier for patients receiving nursing care. During the preoperative period, nurses perform a complete physical assessment of the patient, obtain a complete medical history of the patient, asses for infection, review of results of diagnostic studies and laboratory result.…”
Section: Doing Formentioning
confidence: 99%